Highly Dispersed DPPF Locked in Knitting Hyper‐Crosslinked Polymers as Efficient and Recyclable Catalyst. Issue 21 (4th June 2018) - Tang, Cheng; Zou, Zhijuan; Fu, Yufang; Song, Kunpeng
Abstract: In this study, a novel catalytic system based on the hyper‐cross‐linked 1, 1′‐Bis (diphenylphosphino) ferrocene (HCP‐DPPF) is prepared for effectively removing Cr (VI) from water. Transmission Electron Microscope (TEM), Scanning Electron Microscope (SEM) and X‐ray Photoelectron Spectroscopy (XPS) were employed for the characterization of the catalyst. The surface area of HCP‐DPPF can reach 349.7 m 2 g −1 and the SEM mapping shows that Fe has a good dispersion on the surface of polymer materials. The resulting HCP‐DPPF exhibited remarkable catalytic activity and excellent durability for the Cr (VI) removal and reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) in an aqueous solution. It could reach nearly 100% conversions within several minutes, even when the amount of the catalyst was used as low as 3 mg. Moreover, the HCP‐DPPF can be reused 14 times and still retain high conversion efficiency over 92%. The results illustrate in situ immobilization of DPPF onto hyper‐cross‐linked polymers which improve the stability and electron transfer of the catalyst, while enhancing the activity of HCP‐DPPF toward Cr (VI) removal and reduction of 4‐NP. Abstract : We report a knitting strategy to prepare Fe‐based metal catalyst immobilized on the functionalized hyper‐crosslinked polymers HCP‐DPPF. The skeleton structure ensured the high dispersion of Fe active sites and improved the stability and electron transfer of the catalyst. As a result, the catalyst HCP‐DPPF exhibited excellent activity and cycle performance toward Cr (VI) removal and reduction of 4‐NP.